Extraction of Light Using Random Nanocone on Poly(vinyl-butyral) for Flexible OLEDs - Dong Jun Lee; In Seon Yoon; Cheol Hwee Park; Junhee Choi; Young Wook Park; Byeong-Kwon Ju (Scientific Reports, 2019)
Abstract In this study, we designed a smooth, highly flexible, mechanically robust poly(vinyl-butyral) (PVB)/silver nanowire (AgNW) composite transparent conducting electrode (TCE) integrated with a random nanocone (RNC) to enhance the light extraction of flexible organic light-emitting diodes (OLEDs). The RNC was fabricated by reactive-ion etching (RIE) on AgNW embedded in PVB. As the etching time increased, the size of the RNC became larger. The sheet resistance and transmittance of PVB/AgNW with the RNC was 21.7 Ω/sq and ~87%, respectively. For the PVB/AgNW, the change in sheet resistance was only 2.6% when a 2,000-bend test was performed. The maximum external quantum efficiency was 28.3% when RNC 700 s was used as a green phosphorescent OLED. In addition, for current efficiency and power efficiency, RNC 700 s increased 1.4 times over RNC 0 s. RNC is free of viewing-angle-dependent color and brightness distortion. PVB/AgNW and RNC are practical ways to overcome the brittleness of conventional indium tin oxide and improve the efficiency of flexible OLEDs. Finally, this product is expected to be applied to various flexible optical devices.